Field assessment of yield and its contributing traits in cowpea treated with lower, intermediate, and higher doses of gamma rays and sodium azide - Raina, Aamir; Khan, Samiullah (Frontiers in Plant Science, 2023)
Across the globe, plant breeders of different organizations are working in collaboration to bring preferred traits to crops of economic importance. Among the traits, “high yielding potential” is the most important as it is directly associated with food security and nutrition, one of the sustainable development goals. Food and Agriculture Organization acknowledges plant breeders' role and efforts in achieving local and global food security and nutrition. Recognizing the importance of pulses and increasing pressure on food security, the United Nations General Assembly declared 2016 the “International year of Pulses” owing to their preferred traits such as climate change resilience, wide adaptability, low agriculture input, protein and nutrient-rich crops. Keeping all these developments in consideration, we initiated an induced mutagenesis program by treating cowpea (Vigna unguiculata L. Walp.) with different doses of gamma rays and sodium azide aiming to enhance the yielding potential of an otherwise outstanding variety viz., Gomati VU-89 and Pusa-578. We noticed a substantial increase in mean values of agronomic traits in putative mutants raised from seeds treated with lower and intermediate doses of mutagens. Statistical analysis such as correlation, path, hierarchical clustering analysis (HCA), and principal component analysis (PCA) were used to assess the difference between mutagenized and control populations. A significant and positive correlation of yield with yield attributing traits was recorded. However, among all the yield attributing traits, seeds per pod depicted the maximum direct impact upon yield, and therefore working on this trait may yield better results. A widely used principal component analysis revealed 40.46% and 33.47% of the total variation for var. Gomati VU-89 and var. Pusa-578, respectively. Cluster analysis clustered treated and control populations into separate clusters with variable cluster sizes. Cluster V in the variety Gomati VU-89 and cluster V and VI in the variety Pusa 578 comprised of putative mutants were higher yielding and hence could be recommended for selection in future breeding programs. We expect to release such mutant lines for framer cultivation in Northern parts of India depending on the performance of such high yielding mutant lines at multi-locations.